Ecological sufism concepts in the thought of Seyyed Hossein Nasr (Research, Society and Development, 2020)
Seyyed Hossein Nasr, one of the Islamic thinkers who have a serious concern and deep concern over the occurrence of the ecological crisis. Forest destruction, pollution, water, and air are clear examples that can be seen in life today. According to him, the root of the problem lies in humans as actors, who have lost their sense of awe and concern for themselves and the universe. Such a state is the result of eroding the awareness of the holy. So that for him the ecological crisis is the result of a spiritual crisis. Therefore, the question arises, what is Nasr's attitude about the ecological crisis and his spirituality? How is the concept of ecological Sufism in his thinking? By examining his thoughts, and his works, researchers will analyze with a philosophical approach to answer these problems. This study states, as a result of its findings, that the concept of ecological Sufism is the relationship between Sufism and ecological values by looking at problems in the environmental crisis. Awareness of Sufism-spirituality has an important role in addressing the ecological crisis. The concept of ecological Sufism is an alternative thought to answer the problem of the ecological crisis and the spiritual crisis in modern humans.